THE ROLE OF TOURISM IN DEVELOPING COUNTRIES. THE CASE OF ALBANIA - Drita Kruja; Mariza Lufi; Iris Kruja (European Scientific Journal, ESJ, 2012)
Developing countries and tourism: sometimes we think this combination as a remedy to solve many economic problems. We must instead ask if the tourist activities are able to improve the development of Third World countries, or, rather, their growth can cause damage to these weak economic systems. It must, therefore, understand the circumstances in which tourism can contribute to sustainable development of these territories. The first benefit of tourism is creating jobs and opportunity for people to increase their income and improve their living conditions. But the question is also: What is the price that those countries should pay? The phenomenon of tourism has enormous consequences in terms of environmental, cultural, economic and social cannot be underestimated. A way to be able to have a better and more effective development of tourism in areas of the South is represented from the increment and a proper balance between domestic tourism and international tourism. Several developing countries still have a gross domestic product (GDP) relatively high, so in addition to the poverty that exists in these countries they are going to increase the size of the middle class and the high class, which have a higher propensity to high consumption as tourist consumption.